COMPARATIVE ANALYSIS OF FIRST STEP ON RUNNING SPEED AND PUSHING MOMENTUM IN FLOP STYLE HIGH JUMP BASED ON MOVEMENT BIOMECHANICS: ANALISIS KOMPARASI LANGKAH AWALAN TERHADAP KECEPATAN LARI DAN MOMENTUM TOLAKAN PADA LOMPAT TINGGI GAYA FLOP BERDASARKAN BIOMEKANIKA GERAK - Revaldi Hidayatulloh; Ach. Zayul M; Puji Setyaningsih (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This research aims to analyze the comparison of starting steps with running speed and pushing momentum in the flop style high jump based on motion biomechanics. The difference in initial steps referred to by the author is even steps (4,5,6) and odd steps (5,7,9). This type of research is descriptive comparative using a quantitative approach. The population in this study were high jump athletes. The sample in this study consisted of one person, namely the 1st winner of PORPROV JATIM 2023 in the men's high jump named Farel Wijayanto from Malang City. The data analysis technique in this research uses SPSS 29 with one sample t-test and kinovea software. The results of this research based on the One Sample Test show that in implementing the flop style high jump using a comparison of steps 4, 5, 6, 7, 8, and 9 there is no difference in the speed and momentum of the flop style high jump. It can be interpreted that using the initial step comparison of 4, 5, 6, 7, 8, and 9 does not have a significant effect on the running speed and momentum of the flop style high jump. To get a high jump in the flop style high jump based on movement biomechanics, the athlete must be able to control the frequency and rhythm of steps during the initial run and pay more attention to the last 3 steps, namely from short-long-short and the athlete's body position is slightly inclined to the curve of the initial running path. curved, the last two steps of the running movement from leaning forward are changed to leaning backwards to lower the athlete's center of mass. Meanwhile, athletes must also be able to utilize angular momentum effectively and efficiently by the athlete at the time of take-off to produce maximum rotating motion when the athlete's body flies over the bar.